Non-oxidative decomposition of methane/methanol mixture over mesoporous Ni-Cu/Al2O3 Co-doped catalysts - Awad, A. (Elsevier Ltd, 2018)
Thermocatalytic decomposition of methane (TCD) is reported to be a promising and green route of hydrogen generation, however, the relatively fast catalyst deactivation is the main drawback of this technology. This article reports an attempt to increase the catalyst deactivation time by using Cu promoted Ni-based catalyst, and methanol premixed methane gas as a feedstock. The catalysts were prepared by wet impregnation method and characterized by TGA, BET, XRD, TPR, FESEM, Raman and TEM. An inevitable decline in surface area from 5.15 to 4.52 m2g-1 due to the addition of 15Cu on 50Ni/Al2O3 was due to the agglomeration of particles and pore blockage of Î³ -Al2O3 support. Moreover, the reduction of NiO was shifted towards lower temperature by successful impregnation of Cu promoter. The overlapping peaks of NiO and CuO confirmed the formation of mixed oxides Nix Cu (1-x) O via XRD analysis. The catalytic activity of both catalysts showed that 50Ni-15Cu/Al2O3 resulted in better methane conversion 75 at 1023 K TOS for 6 h. The post reaction analysis of the catalysts revealed that carbon in the form of CNF got deposited on the surface of the catalyst having amorphous and crystalline morphology. Finally, TEM also revealed that GF, CNF, and MWCNF were encapsulated over the surface of 50Ni-15Cu/Al2O3. Â© 2018 Hydrogen Energy Publications LLC